1999
DOI: 10.1080/026404199365687
|View full text |Cite
|
Sign up to set email alerts
|

Exercise, plasma catecholamine concentrations and decision-making performance of soccer players on a soccer-specific test

Abstract: The main aim of this study was to compare the decision-making performance of college soccer players on a soccer-specific, tachistoscopically presented test, at rest and while exercising at their adrenaline threshold and at their maximum power output. These were determined following an incremental test to exhaustion on a cycle ergometer. After the initial maximum power test, participants (n = 9) were allowed 10 habituation trials on the soccer decision-making test. Participants' decision-making performance was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
53
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 23 publications
6
53
2
Order By: Relevance
“…Epinephrine and norepinephrine are proposed to helping to speed up decision making because of their role as neurotransmitters in the central nervous system (McMorris et al, 1999). In a challenge state, the SAM activation represents an attempt to mobilize energy for coping.…”
Section: Performance Consequences In the Tctsamentioning
confidence: 99%
“…Epinephrine and norepinephrine are proposed to helping to speed up decision making because of their role as neurotransmitters in the central nervous system (McMorris et al, 1999). In a challenge state, the SAM activation represents an attempt to mobilize energy for coping.…”
Section: Performance Consequences In the Tctsamentioning
confidence: 99%
“…[32][33][34][35][36][37] But other investigators reported the contrary conclusions: that fatigue either does not affect learning ability, [1][2][3][4][5][6][7][8][9][10][11][12] or indeed facilitates it. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] This question appears to be unresolved at present.…”
Section: Discussionmentioning
confidence: 95%
“…Some previous studies have reported on measurements of learning or cognition tasks after exercise in humans, but the results are contradictory. Some investigators have found ability to be unaffected, [1][2][3][4][5][6][7][8][9][10][11][12] others that it is facilitated by physical fatigue, [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] and yet others have found impairment. [32][33][34][35][36][37] Because of the complex psychological factors present in the human experiments, evaluation of behavioral changes related to physical exhaustion in animal experiments may be a better way to gain insight into the question.…”
mentioning
confidence: 99%
“…Previous research did show that fatigued players still recognise the best action in a given tactical situation (e.g. McMorris & Graydon, 1996a, 1996bMcMorris et al, 1999), but it remains unclear to what extent players would also choose to execute these actions when they are fatigued (Iodice et al, 2017). Taking players' physical capacity and motivation © 2018 The Author(s).…”
mentioning
confidence: 99%
“…Previous studies, however, have often failed to do so. In the 1990s, a series of experiments by McMorris and colleagues generally showed that high levels of exercise (which are likely to induce fatigue) resulted in no effect on the quality of decision-making in soccer (McMorris & Graydon, 1996a, 1996bMcMorris et al, 1999). In these studies, players were shown static tactical game-play situations and had to recognise and verbally indicate the proper action for that situation.…”
mentioning
confidence: 99%